2020
DOI: 10.1038/s41598-020-72789-8
|View full text |Cite
|
Sign up to set email alerts
|

New marine data and age accuracy of the Romualdo Formation, Araripe Basin, Brazil

Abstract: A combined biostratigraphic and palaeoecological study of foraminifera, ostracodes and microfacies was carried out on the Aptian in the Sítio Sobradinho section of the Araripe Basin, northeast Brazil. The analysed section represents a deepening-upward sequence with mid-ramp shoal and outer ramp to basin facies associations on a mixed siliciclastic-carbonate marine ramp. The analysed rocks are dominated by Early Cretaceous planktic foraminifera (Hedbergella aptiana, H. praelippa, H. sigali, Blesfucuiana cf. cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 87 publications
1
31
0
2
Order By: Relevance
“…The first concluded that there are no Albian palynomorphs in the Post-rift Sequence I, which corresponds entirely to the Sergipea variverrucata palynozone. Melo et al (2020), studying ostracods and foraminifers, came to the same conclusion, that is, the sequence in question corresponds to the upper part of the Aptian. In view of this, the present work aims to contribute to this debate, considering biostratigraphic and geochronological analyses, having as a case study the Post-rift Sequence I of the Araripe Basin.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…The first concluded that there are no Albian palynomorphs in the Post-rift Sequence I, which corresponds entirely to the Sergipea variverrucata palynozone. Melo et al (2020), studying ostracods and foraminifers, came to the same conclusion, that is, the sequence in question corresponds to the upper part of the Aptian. In view of this, the present work aims to contribute to this debate, considering biostratigraphic and geochronological analyses, having as a case study the Post-rift Sequence I of the Araripe Basin.…”
Section: Introductionmentioning
confidence: 71%
“…Regali, 1987. However, the very recent works by Arai & Assine (2020) and Melo et al (2020) are the ones that present the most in-depth studies on the age and paleoenvironments of this lithostratigraphic unit.…”
Section: Microfossil Biostratigraphy Of the Post-rift Sequence Imentioning
confidence: 99%
See 3 more Smart Citations